2021
DOI: 10.3389/fbioe.2021.684105
|View full text |Cite
|
Sign up to set email alerts
|

Instant in-situ Tissue Repair by Biodegradable PLA/Gelatin Nanofibrous Membrane Using a 3D Printed Handheld Electrospinning Device

Abstract: Background: This study aims to design a 3D printed handheld electrospinning device and evaluate its effect on the rapid repair of mouse skin wounds.Methods: The device was developed by Solidworks and printed by Object 350 photosensitive resin printer. The polylactic acid (PLA)/gelatin blend was used as the raw material to fabricate in-situ degradable nanofiber scaffolds. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and water vapor permeability tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The MeGel nanofiber mats displayed a taro peak around 20°. When the different mass ratios of MeGel and PLLA were combined into nanofibers, the MeGel/PLLA nanofibers also exhibited a crystallization peak at roughly 16.6° [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MeGel nanofiber mats displayed a taro peak around 20°. When the different mass ratios of MeGel and PLLA were combined into nanofibers, the MeGel/PLLA nanofibers also exhibited a crystallization peak at roughly 16.6° [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the Young’s modulus of our crosslinked MeGel/PLLA nanofiber mats was all more than 30 MPa, which were significantly higher compared to the Gel/PLA un-crosslinked nanofiber mats [ 45 ]. For instance, the Young’s modulus of Gel/PLA nanofiber mats fabricated by Chen et al was only in the range of 0.2–1.37 MPa [ 40 ]. Taken together, the UV crosslinking process was demonstrated to significantly improve the structural stability and mechanical properties of MeGel/PLLA nanofiber mats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the in situ dressings are especially suitable for wounds with irregular shapes. Most recently, Chen et al fabricated a handheld electrospinning device by using a 3D printer, and the gelatin/PLA nanofiber mats were electrospun on the mouse wound site to realize the in situ wound repair by using the as-fabricated handheld electrospinning setup ( Figure 7 ) [ 133 ]. The in vivo results indicated that the in situ electrospun gelatin/PLA nanofiber dressings exhibited an obviously increased repair for the acute injury wound comparing with the commercial gauzes.…”
Section: Electrospun Gelatin-based Nanofiber Mats As Wound Dressingsmentioning
confidence: 99%
“…Other possible candidates for the electrospun polymer solution used for preparing wound dressings include, but are not limited to, zein/thyme essential oil (TEO) [ 199 ], zein/clove essential oil (CEO) [ 200 ], zein and cinnamon oil [ 201 ] and PLA/gelatin [ 202 ]. The essential oil in every combination has antibacterial activity, and some even are active against Escherichia coli and Staphylococcus aureus, as in cinnamon oil with an inhibition zone of around 5 cm.…”
Section: Portable Es Device Applicationsmentioning
confidence: 99%